Improving mathematics learning outcomes using the problem-based learning model for class V students of UPTD SDN 192 BARRU - Hidayatullah S, Muhammad Nurul; Haslinda, Haslinda (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to improve mathematics learning outcomes among fifth-grade students at UPTD SDN 192 Barru by implementing the Problem-Based Learning (PBL) model. The focus of the study is on students' ability to understand and solve decimal multiplication problems. The research employed a classroom action research (CAR) method consisting of three stages: pre-action, Cycle I, and Cycle II. The results indicate that implementing the PBL model significantly enhances students' comprehension of the material. The percentage of students who accurately understood the problems increased from 23% during the pre-action stage to 46% in Cycle I, and finally to 85% in Cycle II. Therefore, it can be concluded that the Problem-Based Learning model is effective in improving students’ mathematics learning outcomes, particularly in decimal multiplication topics.